Dysphoria mundi: le son du monde qui s'écroule - Preciado, Paul B. (Essai français, 2022)
«Dysphoria mundi est un texte mutant, qui hybride essai, philosophie, opéra, poésie et autofiction, afin de rendre compte de la transition planétaire en cours. Ce livre apprend au regard à distinguer ce que la propagande nihiliste mainstream cherche à dissimuler : les déplacements irréversibles qui s'opèrent dans les sphères sociales, politiques, sexuelles. Il n'est pas question d'un passé mythique ni d'un avenir messianique, mais d'un présent révolutionnaire. Le XIXe siècle était hystérique ; le XXe, schizophrène ; notre époque est dysphorique. Anxiété généralisée, troubles post-traumatiques, syndrome de dépendance, dysphorie de genre, destruction légitimée de l'écosystème... Voici l'hypothèse que propose ce livre : généraliser la notion de dysphorie afin de la comprendre non pas comme une maladie mentale, mais comme une dissidence politique. L'auteur organise une archive implacable de la fabrication/destruction nécropolitique de la subjectivité dans la modernité, et dessine une cartographie des pratiques d'émancipation susceptibles de transformer l'avenir. On dit souvent qu'il nous est devenu plus facile d'imaginer la fin du monde que de penser la fin du capitalisme. Preciado persiste à observer les preuves de pratiques alternatives à cette impasse : de nouveaux modes de vie jusqu'alors disqualifiés comme improductifs et anormaux se présentent désormais comme la seule issue.»--Page 4 de la couverture.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; disphorie; har4600; identités LGBTQIA2+; philosophie; premier cycle; périodes historiques; queer; santé; sciences humaines; sexualité; thématiques; transféminisme; études littéraires

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton classic editions, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Beyond Binary: Genderqueer as Critical Gender Kind - Dembroff, Robin (Philosophers' Imprint, 2020)
We want to know what gender is. But metaphysical approaches to this question solely have focused on the binary gender kinds men and women. By overlooking those who identify outside of the binary–the group I call ‘genderqueer’–we are left without tools for understanding these new and quickly growing gender identifications. This metaphysical gap in turn creates a conceptual lacuna that contributes to systematic misunderstanding of genderqueer persons. In this paper, I argue that to better understand genderqueer identities, we must recognize a new type of gender kind: critical gender kinds, or kinds whose members collectively destabilize one or more pieces of dominant gender ideology. After developing a model of critical gender kinds, I suggest that genderqueer is best modeled as a critical gender kind that destabilizes the ‘binary axis’, or the piece of dominant gender ideology that says that the only possible genders are the binary, discrete, exclusive, and exhaustive kinds men and women.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sofia; systèmes d'oppressions; thématiques; états-unis

True loves, dark nights: Queer performativity and grieving through music in the work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)
This dissertation studies the cultural significance of Canadian-American singer/songwriter Rufus Wainwright's (b. 1973) album All Days Are Nights: Songs for Lulu (Decca, 2010). Lulu was written, recorded, and toured in the years surrounding the illness and eventual death of his mother, beloved Quebecoise singer/songwriter Kate McGarrigle. The album, performed as a classical song cycle, stands out amongst Wainwright's musical catalogue as a hybrid composition that mixes classical and popular musical forms and styles. More than merely a collection of songs about death, loss, and personal suffering, Lulu is a vehicle that enabled him to grieve through music. I argue that Wainwright's performativity, as well as the music itself, can be understood as queer, or as that which transgresses traditional or expected boundaries. In this sense, Wainwright's artistic identity and musical trajectory resemble a rhizome, extending in multiple directions and continually expanding to create new paths and outcomes. Instances of queerness reveal themselves in the genre hybridity of the Lulu song cycle, the emotional vulnerability of Wainwright's vocal performance, the deconstruction of gender norms in live performance, and the circulation of affect within the performance space. In this study, I examine the song cycle form, Wainwright's musical score and vocal performance, live performance videos, and fan reactions to live performances in order to identify meaningful moments where Wainwright's musical and performative decisions queer audience expectations. While these musical moments contribute to the already rich and varied lineage of the gay male artist in both classical and popular music, I argue that Wainwright's queer performativity and nontraditional musical choices speak to larger issues important to American culture in the contemporary moment. These issues include the visibility of male public mourning and the healing power of artistic expression in the face of traumatic loss.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; culture populaire; deuil; discipline; genre; mémoires/thèses; philosophie; périodes historiques; queer; ressource en ligne; résistance; sciences humaines; émotions

Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis